Unintended consequences of cigarette price changes for alcohol drinking behaviors across age groups: evidence from pooled cross sections - McLellan Deborah L; Hodgkin Dominic; Fagan Pebbles; Reif Sharon; Horgan Constance M (BMC, 2012)
Abstract Background Raising prices through taxation on tobacco and alcohol products is a common strategy to raise revenues and reduce consumption. However, taxation policies are product specific, focusing either on alcohol or tobacco products. Several studies document interactions between the price of cigarettes and general alcohol use and it is important to know whether increased cigarette prices are associated with varying alcohol drinking patterns among different population groups. To inform policymaking, this study investigates the association of state cigarette prices with smoking, and current, binge, and heavy drinking by age group. Methods The 2001-2006 Behavioral Risk Factor Surveillance System surveys (n = 1,323,758) were pooled and analyzed using multiple regression equations to estimate changes in smoking and drinking pattern response to an increase in cigarette price, among adults aged 18 and older. For each outcome, a multiple linear probability model was estimated which incorporated terms interacting state cigarette price with age group. State and year fixed effects were included to control for potential unobserved state-level characteristics that might influence smoking and drinking. Results Increases in state cigarette prices were associated with increases in current drinking among persons aged 65 and older, and binge and heavy drinking among persons aged 21-29. Reductions in smoking were found among persons aged 30-64, drinking among those aged 18-20, and binge drinking among those aged 65 and older. Conclusions Increases in state cigarette prices may increase or decrease smoking and harmful drinking behaviors differentially by age. Adults aged 21-29 and 65 and older are more prone to increased drinking as a result of increased cigarette prices. Researchers, practitioners, advocates, and policymakers should work together to understand and prepare for these unintended consequences of tobacco taxation policy.